Stunting Prevention Assistance Through Collaboration Between the Government and the Duano Tribe Based on Local Wisdom: Pendampingan Pencegahan Stunting Melalui Kolaborasi Pemerintah dan Suku Duano Berbasis Kearifan Lokal - Ummul Fithriyyah, Mustiqowati; Rahmi Febriyanti; Cahaya Makbul (Universitas Lancang Kuning, 2025)
The prevalence of stunting in Indonesia in 2022 is 21.6%. The issuance of Presidential Regulation of the Republic of Indonesia Number 2 of 2021 concerning the acceleration of stunting reduction is an effort and commitment of the government to accelerate the reduction of stunting. Stunting is a depiction of chronic malnutrition during the growth and development period since the beginning of an individual's life. In Riau Province, the highest prevalence of stunting is in Indragiri Hilir Regency, reaching 28.5%. The purpose of this research-based service is to describe the prevention of stunting through the optimization of local food processing of the remote indigenous community of the Sea Tribe (Duano) in Tanah Merah District, Indragiri Hilir Regency, Riau. This research-based service uses the Asset-based community development (ABCD) approach. The ABCD approach utilizes natural resource assets owned by the community. Data collection was carried out through the stages of observation and interviews with the indigenous community of the Sea Tribe (Duano) where 50 people were involved in this research-based service. The data that has been obtained was analyzed and concluded descriptively. The result of this research-based service is the formation of an integrated nutritional improvement collaboration between the government, health workers, and the Suku Laut (Duano) indigenous community based on local wisdom. This collaboration raises public awareness to strive to prevent stunting through optimizing the use and processing of local food ingredients creatively and innovatively according to nutritional needs.